2012
DOI: 10.1590/s0074-02762012000700012
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in a southern Brazilian prison

Abstract: The occurrence of tuberculosis (TB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
4
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 33 publications
5
27
4
11
Order By: Relevance
“…The prison had typical conditions in terms of layout, crowding, and diagnostic resources. However, other studies have found that TB incidence and transmission rates are even higher in other prisons in Brazil ( 3 , 14 , 15 ). Thus, the contribution of spillover infections to the general community may be even greater.…”
Section: Discussionmentioning
confidence: 79%
“…The prison had typical conditions in terms of layout, crowding, and diagnostic resources. However, other studies have found that TB incidence and transmission rates are even higher in other prisons in Brazil ( 3 , 14 , 15 ). Thus, the contribution of spillover infections to the general community may be even greater.…”
Section: Discussionmentioning
confidence: 79%
“…16 Multiple studies in prisons throughout Brazil have documented active TB prevalence in excess of 2,000 cases per 100,000 inmates. 14,[17][18][19][20] The central west state of Mato Grosso do Sul has the highest incarceration rate in the country. In this setting, we obtained empirical data on architecture, ventilation, and occupancy and projected the impact of diagnostic and environmental interventions on TB transmission.…”
Section: Introductionmentioning
confidence: 99%
“…, 30 , 34 As discussed, this population consists predominantly of young adults from socioeconomically disadvantaged communities with high rates of active tuberculosis. Among other elements posing an increased risk for the development of tuberculosis, the rate of alcoholism (24.8%) was lower than that reported in other studies (39.2-44.1%), 30 whereas the rate of smoking (61.1%) was similar 30 .…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 27 , 34 , 36 Therefore, it is important to detect LTBI in the HIV-infected population so that preventive measures can be taken, because HIV-infected individuals with LTBI have an 8.0-10.0% annual risk of developing active tuberculosis, as do users of inhaled illicit drugs with LTBI. In contrast, HIV-uninfected individuals with LTBI have a 10.0% lifetime risk of developing tuberculosis 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation